Effect of injectable equine collagen type I on metabolic activity and apoptosis of gingival fibroblasts - Klewin-Steinböck, Sylwia; Nowak-Terpiłowska, Agnieszka; Adamski, Zygmunt; Grocholewicz, Katarzyna; Wyganowska-Świątkowska, Marzena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Collagen as a biomaterial is widely used for tissue regeneration due to various advantages including its biodegradation, biocompatibility, and low allergenicity. Along with aesthetic medicine development, collagen is also used in the injectable form as a tissue biostimulator. The area of our study was collagen’s impact on fibroblast activity and apoptosis. The research showed that atelocollagen decreases metabolic activity of fibroblasts, but also showed an increasing number of living cells after 48 h and 72 h incubation under the influence of collagen.